2014
DOI: 10.1371/journal.pone.0085672
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mixed Transplantation of Autologous and Allogeneic Microskin Grafts on Wound Healing in a Rat Model of Acute Skin Defect

Abstract: The treatment of extensive thermal injuries with insufficient autologous skin remains a great challenge to burn surgeons. In this study, we investigated the influence of the ratio of autologous and allogeneic tissue in mixed microskin grafts on wound healing in order to develop an effective method for using limited donor skin to cover a large open wound. Four different mixtures were tested: autologous microskin at an area expansion ratio of 10∶1 with allogeneic microskin at an area expansion ratio of 10∶1 or 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
0
4
0
6
Order By: Relevance
“…At our institute, microskin grafting was performed regularly in patients who had limited autografts by using the reported methods with some modifications. We found that a microskin graft with an area expansion ratio of 10:1 achieved the best wound healing effect [ 25 , 26 ]; thus, the microskin graft could partly solve the problem of covering extensive burned wounds with small areas of autografts [ 27 , 28 ].…”
Section: Reviewmentioning
confidence: 99%
“…At our institute, microskin grafting was performed regularly in patients who had limited autografts by using the reported methods with some modifications. We found that a microskin graft with an area expansion ratio of 10:1 achieved the best wound healing effect [ 25 , 26 ]; thus, the microskin graft could partly solve the problem of covering extensive burned wounds with small areas of autografts [ 27 , 28 ].…”
Section: Reviewmentioning
confidence: 99%
“…Most commonly, collagen gels change their shape irreversibly in response to the contractile action of encapsulated cells. [30] Consequently, transplanted collagen gels may contract, leading to delayed graft integration, [31] tissue deformation, [32] and scar contracture. [33,34] In order to determine the ability of fPA functionalisation in circumventing this effect, we tested changes in shape from +fPA and control collagen gels containing encapsulated hCSFs.…”
Section: Contraction Of Fpa-functionalised Collagen Gels Containing Ementioning
confidence: 99%
“…The most abundant constitutive integrins in the epidermis are β1 and high expressed β 1 ‐integrins can prompt epidermal cells into a high proliferative and dedifferentiated state . The characterization of integrin β1‐deficient mice has revealed crucial roles for the β1 integrin subfamily in hair follicle development, skin integrity, and cutaneous wound repair . More importantly, the integrin β1 subunit has been found to be a marker of keratinocyte stem cells (KSCs) and is the usual means of identifying such cells .…”
Section: Discussionmentioning
confidence: 99%